The future of innovation and technology in education : policies and practices for teaching and learning excellence - Visvizi, Anna, 1976-; Lytras, Miltiadis D., 1973-; Daniela, Linda, 1967- (Emerald studies in higher education, innovation and technology, 2018)
This book explores the effective use of information and communication technology (ICT) in teaching and learning. Concept-laden and practice-driven discussions offer insights into the art and practice of employing virtual and augmented reality (VR/AR), electronic devices, social networks and massive open online courses (MOOCs) in education.